Color Image Processing - Edoardo Provenzi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
What we call the "color" of an object is the result of a very complicated and not yet fully understood mechanism that involves the interaction between the light reflected by the object surface and the eyes, and the subsequent analysis of the retinal signal by the brain. For these reasons, research into color is intrinsically multidisciplinary and can be conducted from many points of view. The contributions presented in this book reflect this spirit, ranging from rigorous mathematical models of color geometry, to the psychophysical discussion of chromatic visual illusion, passing through state-of-the-art computational models in color enhancement. The idea behind this book is to give the reader an idea of the richness and variety of the research into color, proving it to be one of the most fascinating interdisciplinary research fields in contemporary science.